Stone clearance rate in patients treated with open surgery versus percutaneous nephrolithotomy for the management of staghorn renal calculi. - Ajmal Khan; Tanzeel Gazder; Nisar Ahmed; Hafiz Saad; Syed Rabiullah; Mazahir Zulfiqar; Usman Qamar; Sanjeet Therani; Hamza Akhter; Saeed Abidi; et al. (International Journal of Endorsing Health Science Research, 2023)
Background: Urinary calculi, particularly staghorn renal calculi, pose a significant health challenge. Percutaneous nephrolithotomy (PCNL) and open surgery are two distinct surgical interventions employed for treating staghorn renal calculi. This study aimed to compare the stone clearance rates of patients undergoing open surgery versus percutaneous nephrolithotomy at the Department of Urology, Sindh Institute of Urology and Transplantation (SIUT) in Karachi, Pakistan. Methodology: A prospective cohort study was conducted from February 8th to August 7th, 2019. Patients aged 18 to 60 years, diagnosed with staghorn renal calculi, were included. Patients with other renal stones and untreated urinary tract infections were excluded. The study enrolled 230 patients, divided into two groups: Group I underwent percutaneous nephrolithotomies, and Group II underwent open surgery. Stone clearance was assessed through post-surgery X-ray KUB. Results: The mean age of participants was 44.99 years, with a balanced gender distribution. Both PCNL and open surgery achieved stone clearance rates of 68.7%, with significantly higher rates observed in the PCNL group (74.8% vs. 62.6%, p = 0.04). Stratification by age, gender, illness duration, and stone location did not yield substantial variations in stone clearance rates. Conclusion: PCNL demonstrated a superior stone clearance rate compared to open surgery in the treatment of staghorn renal calculi. This finding highlights the potential of PCNL as a more effective intervention for addressing this challenging urological condition.